Selenium transport in plants with a special focus on selenium hyperaccumulators - Trippe, Richard Croxall, III, author; Pilon-Smits, Elizabeth, advisor; Pilon, Marinus, advisor; Peebles, Christie, committee member; Schiavon, Michela, committee member (Colorado State University. Libraries, 2021)
The aims of this thesis are to synthesize current knowledge of selenium (Se) transport and metabolism in plants and improve understanding of Se transport in a class of plant species known as Se hyperaccumulators (HAs). These Se HAs can accumulate Se at up to 1,000 times higher concentrations than normal plants by utilizing specialized systems of Se transport and metabolism. The first chapter of this thesis constitutes a review of the current knowledge about Se transport and metabolism in plants, with a focus on implications for biofortification and phytoremediation. Selenium is a necessary human micronutrient, and around a billion people worldwide may be Se deficient. This can be ameliorated by Se biofortification of staple crops. Selenium is also a potential toxin at higher concentrations, and multiple environmental disasters over the past 50 years have been caused by Se pollution from agricultural and industrial sources. Phytoremediation by plants able to take up large amounts of Se is an important tool to combat pollution issues. Both biofortification and phytoremediation applications require a thorough understanding of how Se is taken up and metabolized by plants. Selenium uptake and translocation in plants is largely accomplished via sulfur (S) transport proteins. Current understanding of these transporters is reviewed here, and transporters that may be manipulated to improve Se uptake are discussed. Plant Se metabolism also largely follows the S metabolic pathway. This pathway is reviewed here, with special focus on genes that may be manipulated to reduce the accumulation of toxic metabolites or enhance the accumulation of nontoxic metabolites. Finally, unique aspects of Se transport and metabolism in Se HAs are reviewed. Selenium hyperaccumulation mechanisms and potential applications of these mechanisms to biofortification and phytoremediation are presented. The second chapter of this thesis covers the results of experimental studies expressing putative Se HA transporter proteins in a yeast (Saccharomyces cerevisiae) model system. Selenium hyperaccumulators are able to take up Se from the soil at concentrations many times higher than other native vegetation. Hyperaccumulators also show evidence of enhanced Se-specificity relative to sulfur. The mechanism for this Se specificity is investigated in this study. We hypothesize that in hyperaccumulators one or more sulfate transport proteins has evolved greater preference for the Se analog, selenate. This study focuses on putative root-to-shoot sulfate/selenate transport proteins SpSULTR2;1 and SpSULTR3;5 from Se hyperaccumulator Stanleya pinnata (Brassicaceae). The coding regions of these genes were amplified via reverse transcription polymerase chain reaction (RT-PCR), cloned in a yeast expression vector and sequenced. SpSULTR2;1 and SpSULTR3;5 were found to be 678 and 638 amino acids in length, respectively. Both proteins showed the characteristic N-terminal cytosolic domain, 12 membrane-spanning domains, and C-terminal cytosolic STAS (Sulphate Transporter and Anti-Sigma factor antagonist) domains. SpSULTR2;1 and SpSULTR3;5 were assayed for selenate specificity by quantifying their relative selenate and sulfate uptake capacities in baker's yeast (Saccharomyces cerevisiae). This assay was complemented with selenate-dependent growth curves in liquid media and a selenate tolerance assay on solid media. Both SpSULTR2;1 and SpSULTR3;5 were expressed by the yeast cells, determined by dot-blot immunoassay. Expression of SpSULTR2;1 effected a slight but non-significant increase in the Se concentration in the yeast relative to the empty vector control in a 1-hour uptake assay when exposed to 1 mM selenate, but not when exposed to 0.1 mM selenate. SpSULTR3;5 was not able to increase the selenate concentration in the yeast relative to the control in the uptake assay. Yeast expressing SpSULTR2;1 or SpSULTR3;5 demonstrated similar selenate tolerance to empty-vector controls. Expression of SpSULTR3;5 or SpSULTR2;1 also did not significantly affect growth relative to the control in liquid media. In conclusion, more studies are needed to determine with certainty whether SpSULTR2;1 or SpSULTR3;5 have selenate-specific transport capability.
Keywords: Stanleya; selenium; SULTR